Ubiquitous and Mobile Learning in the Digital Age
XXXIV, 294 p.
Keywords: This edited volume includes the most up to date, expanded, and peer reviewed papers from the 2011 CELDA Conference, focusing on the conference theme: Ubiquitous and Mobile Informal and Formal Learning in thr Digital Age. The contributions are aggressively interdisciplinary and cover such timely topics as social web technologies, virtual worlds and games, and location-based and context-aware learning environments. Informal and formal learning settings are explored and a myriad of concrete examples provided to assit the reader in developing curricula, programs, and courses on the topic. .